Rehabilitation of Critical Land Through Implementation of Four-Dimensional Agroforestry in Tenjolaya, Bogor, West Java - Hartoyo, Adisti Permatasari Putri; Madani, Hilmi Naufal; Muhammad, Dimas Nur; Hasanah, Asmaul; Ghalib, Ammar; Alifioni, Kintan (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
Critical land is caused by unsustainable land use and has an impact on decreasing the function of the land ecosystem. An effort to rehabilitate critical land can be carried out through the implementation of four-dimensional agroforestry (4D Agroforestry). The aims of this research were i) to design a 4D Agroforestry design, and ii) to analyze the growth of ginger (Zingiber officinale), pepper (Piper nigrum), cardamom (Amomum cardamomum), and grass jelly (Cyclea barbata) under the shade of mahogany (Swietenia mahagony) . The number of plants used was 67 ginger seeds, 44 pepper seeds, 187 grass jelly seeds, and 65 cardamom seeds, so the total was 363 plant seeds with an observation duration of 4 WAP. Implementation of 4D Agroforestry is an alternative effort to optimize land management by utilizing 4 dimensions, namely i) length dimension by planting mahogany, ii) width dimension by planting grass jelly (C. barbata), iii) height dimension by planting pepper ( P. nigrum), cassava (M. esculenta), ginger (Z. officinale), and cardamom (Amomum cardamomum), as well as iv) time dimensions for short-term production (production from cassava, grass jelly, ginger and cardamom plants ), medium (production from pepper plants), and long (production from mahogany wood) to achieve sustainable production. Cardamom plants produced the best growth in the parameters of height increase (15.28 cm) and percent survival (98.46%) after 4 WAP. Keywords: agroforestry, farmers, rehabilitation